2002
DOI: 10.1097/00005792-200211000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Secular Trends of Candidemia Over 12 Years in Adult Patients at a Tertiary Care Hospital

Abstract: The incidence of fungal infections has been increasing for the last 3 decades, especially among neutropenic, cancer, and critically ill patients. These infections are associated with high mortality rates. We retrospectively reviewed medical charts of adult patients with fungemia from 1989 to 2000 at our institution. The characteristics of the population groups served by the hospital were described. Of 328 patients with fungemia, we reviewed 315 (96%) medical records, and focused on those with candidemia (n = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
70
1
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(83 citation statements)
references
References 62 publications
8
70
1
4
Order By: Relevance
“…Incidence rates of critical care unit candidaemia in previous studies have varied from 1.1 to 94 cases per 1000 admissions, depending upon the geographic location of the unit, setting and inclusion criteria for the study. 25,[51][52][53][54][55][56] The rate of IFD in blood in the present study, at 3.5 per 1000 admissions, is similar to that of other European critical care units. 51,54,57 A previous hospital-wide surveillance from six sentinel hospitals in the UK identified that 45% of candidaemia was reported from the critical care unit, corresponding with an incidence of 7.4 per 1000 admissions.…”
Section: Discussionsupporting
confidence: 75%
“…Incidence rates of critical care unit candidaemia in previous studies have varied from 1.1 to 94 cases per 1000 admissions, depending upon the geographic location of the unit, setting and inclusion criteria for the study. 25,[51][52][53][54][55][56] The rate of IFD in blood in the present study, at 3.5 per 1000 admissions, is similar to that of other European critical care units. 51,54,57 A previous hospital-wide surveillance from six sentinel hospitals in the UK identified that 45% of candidaemia was reported from the critical care unit, corresponding with an incidence of 7.4 per 1000 admissions.…”
Section: Discussionsupporting
confidence: 75%
“…In contrast, we report a high proportion of C. tropicalis (21%) candidemia, even in neonates. European and North American series have consistently reported low proportions of C. tropicalis candidemia (2 to 10% in Europe and 10 to 12% in the United States and Canada) (3,4,6,13,16,22,26,28,30,37,42,47,50,51), whereas higher proportions were observed in a study from Saudi Arabia (20.7%) (1). In our study, the proportion varied from 16 to 29% among the different centers.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, an increasing incidence of candidemia in Iceland has been observed during the period between 1980 and 1999 (6). On the other hand, data obtained from a national surveillance study conducted in Swiss tertiary-care hospitals suggested that the incidence of candidemia remained unchanged during the period of 1991 to 2000 (28), while a singlecenter study from Switzerland reported decreasing incidence rates (16). It seems therefore that differences do exist in the epidemiology of candidemia between different countries, underscoring the need for continuous surveillance to monitor trends in incidence, species distribution, and antifungal drug susceptibility profiles.…”
mentioning
confidence: 99%
“…Existen diversos reportes describiendo a las especies de Candida entre los cinco aislados más frecuentes en hemocultivos en infecciones intrahospitalarias en Estados Unidos de América (E.U.A.) y países desarrollados 1 . Su incidencia varía entre 0,035 y 0,15/1.000 pacientes/día de estancia hospitalaria (DEH), en series norteamericanas y europeas [2][3][4] .…”
Section: Introductionunclassified